Evaluation of Anti-HIV-1 Integrase and Anti-Inflammatory Activities of Compounds from Betula alnoides Buch-Ham - Prapaporn Chaniad; Teeratad Sudsai; Abdi Wira Septama; Arnon Chukaew; Supinya Tewtrakul (Advances in Pharmacological Sciences)
Betula alnoides is a medicinal plant in Thai traditional longevity preparations. The crude extracts of this plant possess various biological activities. However, the isolated compounds from this plant have no reports of anti-HIV-1 integrase (IN) activity. Therefore, the present study aims to investigate the anti-HIV-1 integrase and anti-inflammatory effects of isolated compounds from this plant and predict the interaction of compounds with integrase active sites. From the bioassay-guided fractionation of the ethanol extract of B. alnoides stems using chromatographic techniques, five pentacyclic triterpenoid compounds were obtained. They are betulinic acid (1), betulin (2), lupeol (3), oleanolic acid (4), and ursolic acid (5). Compound 2 exhibited the most potent inhibitory activity against HIV-1 IN, with an IC50 value of 17.7 μM. Potential interactions of compounds with IN active sites were investigated using computational docking. The results indicated that active compounds interacted with Asp64, a residue participating in 3′-processing, and Thr66, His67, and Lys159, residues participating in strand-transfer reactions of the integration process. Regarding anti-inflammatory activity, all compounds exerted significant inhibitory effects on LPS-induced nitric oxide production (IC50 < 68.7 μM). Thus, this research provides additional scientific support for the use of B. alnoides in traditional medicine for the treatment of HIV patients.